Study of Strong Turbulence Effects for Optical Wireless Links - ÇALLIALP, FULYA (SPIE-INT SOC OPTICAL ENGINEERING, 2012)
Strong turbulence measurements that are taken using real time optical wireless experimental setups are valuable when studying the effects of turbulence regimes on a propagating optical beam. In any kind of FSO system, for us to know the strength of the turbulence thus the refractive index structure constant, is beneficial for having an optimum bandwidth of communication. Even if the FSO Link is placed very well-high-above the ground just to have weak enough turbulence effects, there can be severe atmospheric conditions that can change the turbulence regime. Having a successful theory that will cover all regimes will give us the chance of directly processing the image in existing or using an additional hardware thus deciding on the optimum bandwidth of the communication line at firsthand. For this purpose, Strong Turbulence data has been collected using an outdoor optical wireless setup placed about 85 centimeters above the ground with an acceptable declination and a path length of about 250 meters inducing strong turbulence to the propagating beam. Variations of turbulence strength estimation methods as well as frame image analysis techniques are then been applied to the experimental data in order to study the effects of different parameters on the result. Such strong turbulence data is compared with existing weak and intermediate turbulence data. Aperture Averaging Factor for different turbulence regimes is also investigated.
Keywords: Free Space Optical Communication; Optical Wireless Link; Strong Turbulence; refractive index structure constant C-n(2); Aperture Averaging; intensity variance; SYSTEM